The implementation of guideline during demolition work by local authority / Mohd Hadibi Bohari. - Bohari, Mohd Hadibi (2010)
Demolition is one of the important works in construction work. Demolition being use if the function of the building is cannot be use anymore because the function of the building itself is not function or the building itself being use for another project for the any of the construction. This research is to aim the objective for the procedure of the demolition work, the problem and issue arise during demolition work, and to give recommendation about the implementation of the guideline during demolition work. The issue of the demolition arise when the demolition of Jaya supermarket and shop house at Perak been collapse during the process of the demolition process. This research to been aim through 3 local authorities in Malaysia, where Dewan Bandaraya Kuala Lumpur ( DBKL ), Majlis Bandaraya Petaling jaya ( MBPJ ) and Majlis Daerah Kuala Langat being selected by this case study to analyze and to achieve the objective. Through this research the method being chosen in interview shows that the process of demolition approval in this Local authority is majority use a building plan approval as a procedures and process of approval the demolition. This is because the approval doesn't have a proper process. The issue and the problem during demolition work. This research has been use an interview by 3 local authorities and questionnaire for adjacent neighbour as a respondent to find the analysis. From the analysis it shows that the problem that normally occurs is the method of chosen, pollution and the resident of the building. It shows that 100% of the neighbors said that demolition give an implementation to the neighbors, and the observations by the local authority is not frequently taken an important. For the conclusion it shows that the local authority needs to take an action in their duties, and observation to avoid the collapsed happen and make and act or code of practice by referring any of the country that have an experience about the demolition work to make the procedures.